Metal Oxide Nanoparticles: Potential Uses in Biomedical Applications - Ficai, Denisa; Oprea, Ovidiu; Ficai, Anton; Maria Holban, Alina (Current Proteomics, 2014)
Metal oxide nanoparticles are becoming increasingly important as one of the newest class of materials used in drugs industry and other health related applications. Both ZnO and Fe3O4 nanoparticles are non-toxic, highly biocompatible and are currently under intense investigation. Antibacterial activity of ZnO makes it suitable for external use as it is in topical applications such as wound dressings and coatings for various medical devices to prevent biofilms formation. The antibacterial activity of ZnO is strongly influenced by size, dispersibility or presence of light. On the other hand the magnetic nature of Fe3O4 makes it suitable for a broader range of application such as magnetic resonance imaging contrast agents, hyperthermia therapy of tumors, bioseparation or targeted drug delivery. In addition, coated Fe3O4 can be loaded with various drugs and find its way into antibacterial and antifungal applications. The current review aims to highlight the latest knowledge about potential uses of such oxide nanoparticles in biomedical application.
Keywords: MRI agents